Carcinoma in situ of the cervix in Brazil: Epidemiology, management and follow-up - Traiman, P. [UNESP]; De Luca, L. A. [UNESP]; Barione, V. [UNESP]; Bacchi, C. E. [UNESP] (My University, 1995)
Ninety-seven patients with carcinoma in situ (CIS) of the cervix were studied between 1972 and 1992. The mean age was 40.8 years, and 89.6% of the patients were white. The first sexual intercourse occurred at the mean age of 18.4 years. The mean number of pregnancies and deliveries were, respectively, 6.12 and 5. Pap smears were negative in 10.7%, and only 60% showed abnormal colposcopic findings, and conization confirmed the CIS diagnosis in 92% of the patients. Hysterectomy, carried out in (77.3%) of our patients, was deemed to be the best treatment for CIS because of its low recurrence rate.
Keywords: Carcinoma in situ (CIS); Cervical intraepithelial neoplasia (CIN); Colposcopy; Conization; Hysterectomy